KONSTRUKSI KEILMUAN HUKUM EKONOMI ISLAM PENDEKATAN TEORI SISTEM JASSER AUDA - Fahrul Ulum (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2015)
This paper highlights an attempt to construct an Islamic economics law by utilizing the system theory approach triggered by Jasser Auda. The core of this paper is to answer how the scientific law of Islamic economy is built so as to meet the goals of science itself, namely the creation of the more holistic of Islamic economics law, non-reductionist, morality, and non-literal. It also emphasizes on multi-dimensions rather than solely one-dimension, multi-value rather than merely comparing, reconstruction rather than deconstruction, theological discussion rather than causality discussion. The construction of the Islamic economics law is consistently run out by functioning the system on the fundamental principles namely validating all cognitions, openness, holistic, multi-dimensionality, and purposefulness.